2018
DOI: 10.17511/jopm.2018.i02.13
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of altered cervical cytological pattern: Aretrospective study in females visiting tertiary care hospital

Abstract: Background: Cervical cancer is one of the major causes of morbidity and mortality in India. Pap smear is a simple, noninvasive, cost-effective and sensitive tool to detect various non-neoplastic and neoplastic lesions of cervix. The objective of this study was to estimate the prevalence of cervical cytological pattern in a tertiary care centre; by using conventional Papanicolaou (Pap) smears for the screening of inflammatory, premalignant and malignant lesions of the cervix. Methods: This cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
3
0
0
Order By: Relevance
“…On cytological examination, 863 (84%) were found satisfactory and 154 cases (15%) were unsatisfactory. This finding was in concordance with the study conducted by Sharma HB et al, 18 Gidwani RK et al 19 NILM was the most common cytological finding, seen in 833 females (96.8%). Epithelial cell abnormality was seen in 30 cases (3.2%) included ASCUS in 0.6% cases, ASC-H in 0.2% cases, LSIL in 1.3% cases and HSIL in 1.0% case.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…On cytological examination, 863 (84%) were found satisfactory and 154 cases (15%) were unsatisfactory. This finding was in concordance with the study conducted by Sharma HB et al, 18 Gidwani RK et al 19 NILM was the most common cytological finding, seen in 833 females (96.8%). Epithelial cell abnormality was seen in 30 cases (3.2%) included ASCUS in 0.6% cases, ASC-H in 0.2% cases, LSIL in 1.3% cases and HSIL in 1.0% case.…”
Section: Resultssupporting
confidence: 93%
“…Single case of Squamous Cell Carcinoma was also seen in female of more than 50 year of age. The results are similar with the findings of Bal MS et al 12 ,Gupta K et al 20 and Gidwani RK et al 19 as they showed that maximum cases of LSIL was found in 40-49 year age group while HSIL and SCC was found in females above 50 years of age.…”
Section: Resultssupporting
confidence: 91%
“…Similar findings were observed by Reddy et al, and Nikumbh et al 1 Majority of the smears (96.3%) were reported Negative for intraepithelial lesion or malignancy. The findings were comparable to those observed by Mulay et al, Bhavani et al, Das et al and Gupta et al 22,25,29,31 Various infectious lesions were also comparable with other studies. In present study, bacterial vaginosis was the most common infectious lesion (23.6%) which was comparable with the study of Malpani et al and Ranabhat et al 8,32 Viral changes were seen in 0.4% in present study which was comparable with the study of Nikumbh et al 1 and the study of Ranabhat et al 8 Follicular cervicitis were seen in 0.1% in present study which was comparable with the study of Mulay et al 22 Mixed infection were seen in 2% in Mulay et al and 0.47 % in Ranabhat et al, whereas 0.43% in present study.…”
Section: Resultssupporting
confidence: 92%